1995
DOI: 10.1111/j.1468-1331.1995.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical intra‐ and interfamilial variability of cluster headache

Abstract: Our recent description of a 17- and 2-fold increased risk of cluster headache among first- and second-degree relatives, respectively, strongly suggests that cluster headache has a genetic cause. Eighteen families with familial occurrence of cluster headache according to the criteria of the International Headache Society were included. Clinical intra- and interfamilial variability of cluster headaches was analyzed in 44 cases (31 males and 13 females) from 18 families. None of the families showed a distinctive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…This result agrees with our previous survey in an Italian case series of 691 patients [5]. Russell and Andersson [8] in their study found that mean age of onset was lower in the patients' children than in their parents; the authors concluded that the presence of possible genetic components may anticipate CH onset.…”
Section: Discussionsupporting
confidence: 82%
“…This result agrees with our previous survey in an Italian case series of 691 patients [5]. Russell and Andersson [8] in their study found that mean age of onset was lower in the patients' children than in their parents; the authors concluded that the presence of possible genetic components may anticipate CH onset.…”
Section: Discussionsupporting
confidence: 82%
“…In the present family the occurrence of typical cluster headache, chronic pain episodes without autonomic manifestations, and episodic oculo‐nasal autonomic outbursts without pain, suggest a common pathogenetic background, probably subserved by the same genetic defect. Episodic and chronic cluster headache have been reported previously in a single family (5).…”
Section: Discussionmentioning
confidence: 81%
“…It is well known that sporadic cases of CH display a marked male preponderance, as mentioned in the Introduction. On the other hand, the ratio between men and women is as low as 1.2 : 1 in familial CH (23, 25–28, 59) and 2.5 : 1 in a recent British clinic population (10). A recent Italian study described a CH family with eight affected and a male : female ratio of 1 : 3 (61).…”
Section: Discussionmentioning
confidence: 99%